Search for CP violation in the phase space of D 0 → K S 0 K ± π ∓ decays with the energy test - Aaij, R; Abdelmotteleb, ASW; Abellan Beteta, C; Abudinén, F; Ackernley, T; Adeva, B; Adinolfi, M; Adlarson, P; Afsharnia, H; Agapopoulou, C; Aidala, CA; Ajaltouni, Z; et al. (Springer, 2024)
A search for CP violation in D0→KS0K+π− and D0→KS0K−π+ decays is reported. The search is performed using an unbinned model-independent method known as the energy test that probes local CP violation in the phase space of the decays. The data analysed correspond to an integrated luminosity of 5.4 fb−1 collected in proton-proton collisions by the LHCb experiment at a centre-of-mass energy of s = 13 TeV, amounting to approximately 950 thousand and 620 thousand signal candidates for the D0→KS0K−π+ and D0→KS0K+π− modes, respectively. The method is validated using D0 → K−π+π−π+ and D0→KS0π+π− decays, where CP-violating effects are expected to be negligible, and using background-enhanced regions of the signal decays. The results are consistent with CP symmetry in both the D0→KS0K−π+ and the D0→KS0K+π− decays, with p-values for the hypothesis of no CP violation of 70% and 66%, respectively.